Tales From Two Neighbors : Productivity Growth in Canada and the United States - Cerisola, Martin (IMF Working Papers; Working Paper, 2000)
This paper assesses productivity trends in Canada vis-a-vis the United States from two perspectives. The first one is based on estimates of total factor productivity. The second one decomposes productivity growth into two sources: investment-specific technical change, associated with improvements in the quality of the capital stock, and neutral technical change, associated with the organization of productive activities. The results indicate that investment-specific technical change is the major underlying cause of the pickup in productivity in Canada and the narrowing of the productivity gap with the United States.